As Compared to What?1and2 - Morrison, Alan B. (Revista Amagis Jurídica, 2025)
When my students tell me that they do not like a particular result in a case, I ask them, “As compared to what?” meaning that if you do not like this outcome, what is your alternative? The U.S. Supreme Court has been on a crusade to tear down the federal administrative state as it has operated at least since 1946 when Congress passed the Administrative Procedure Act (APA). But the Court seems to be doing so without providing a workable way to administer the laws that Congress has enacted to solve serious problems in our society.